2020
DOI: 10.1177/0885066620960629
|View full text |Cite
|
Sign up to set email alerts
|

Providing Evidence-Based Care, Day and Night: A Quality Improvement Initiative to Improve Intensive Care Unit Patient Sleep Quality

Abstract: Objective: Evidence-based guidelines recommend promoting sleep in the Intensive Care Unit (ICU), yet many patients experience poor sleep quality. We sought to engage allied health staff and patient families to determine barriers to sleep promotion, to measure sleep quality for ICU patients, and to evaluate the improvement in sleep quality after implementation of nursing morning report protocol and a doorway poster. Design: The study followed an interrupted time-series framework of quality improvement. Qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Patients in the post-protocol group were more likely to receive MV compared to patients in the preprotocol group (55.7% vs 36.1%; P < .001). MV days were similar between the 2 groups (5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) pre-protocol vs 4 (3-9) post-protocol; P = .053).…”
Section: Secondary Outcomesmentioning
confidence: 88%
See 1 more Smart Citation
“…Patients in the post-protocol group were more likely to receive MV compared to patients in the preprotocol group (55.7% vs 36.1%; P < .001). MV days were similar between the 2 groups (5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) pre-protocol vs 4 (3-9) post-protocol; P = .053).…”
Section: Secondary Outcomesmentioning
confidence: 88%
“…4 Polysomnography demonstrates that critically ill adults experience increased sleep fragmentation and daytime sleep, decreased restorative sleep, frequent arousals and awakenings, and abnormal sleep architecture. 5 Common barriers to sleep in the ICU include frequent awakenings for procedures, vital sign checks, medication administration, mechanical ventilation (MV), inappropriate and artificial light, increased noise levels, anxiety, and pain. 1 Sleep-enhancing medications lack safety and efficacy data in the critically ill population and may increase the risk for polypharmacy and delirium rather than actually promote sleep.…”
Section: Introductionmentioning
confidence: 99%
“…In the tracheostomized subjects, melatonin and neuroleptic agents were preferred each in about 20% of patients. Other investigators have reported a very variable use of sleep medication in 13% to 58% of ICU-patients [ 12 , 22 , 39 ].…”
Section: Discussionmentioning
confidence: 99%